2016
DOI: 10.1002/prca.201600069
|View full text |Cite
|
Sign up to set email alerts
|

The protein inventory of Clostridium difficile grown in complex and minimal medium

Abstract: The intestinal pathogen Clostridium difficile is causing an increasing number of infections often characterized by severity and high relapse rates. Profound knowledge of the physiology of the pathogen could help to develop new treatment strategies. Proteomics, a valuable tool to study bacterial physiology, was used in this work to establish a benchmark proteome of reference strain C. difficile 630Δerm with MS-based details on all identified proteins. Our elaborate annotation and visualization of C. difficile 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…The Perseus software platform [34] was used to carry out ANOVA testing and to generate heatmaps on the basis of DESeq2 rlog transformed count data. Voronoi treemaps of DESeq2 data were constructed using the Paver software (DECODON GmbH, Germany) based on an assignment of corresponding gene products to TIGRFAM roles [35] as described recently [36].…”
Section: Feature Quantification and Detection Of Differentially Exprementioning
confidence: 99%
See 2 more Smart Citations
“…The Perseus software platform [34] was used to carry out ANOVA testing and to generate heatmaps on the basis of DESeq2 rlog transformed count data. Voronoi treemaps of DESeq2 data were constructed using the Paver software (DECODON GmbH, Germany) based on an assignment of corresponding gene products to TIGRFAM roles [35] as described recently [36].…”
Section: Feature Quantification and Detection Of Differentially Exprementioning
confidence: 99%
“…Cells were lyzed, protein cysteine residues were differentially labeled according to the diaCys approach and the proteins were then separated via SDS-PAGE according to Sievers et al [37]. Gel lanes were cut into 10 slices, proteins trypsinized in-gel, peptides eluted and desalted as described previously [36].…”
Section: Differential Isotopic Alkylation Of Cysteine (Diacys) and Msmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we observed a high abundance of oxidative stress-related proteins in C. difficile 630erm already at conditions devoid of any oxidizing agents (6) and no significant induction when the bacterium was shifted to micro-aerobic conditions (7). Several of the corresponding genes are encoded at one genetic locus comprising a rubrerythrin (rbr1), the transcriptional repressor PerR (perR), a desulfoferrodoxin (rbo) and a glutamate dehydrogenase with an N-terminal rubredoxin fold (CD630_08280).…”
Section: Resultsmentioning
confidence: 82%
“…Several of the corresponding genes are encoded at one genetic locus comprising a rubrerythrin (rbr1), the transcriptional repressor PerR (perR), a desulfoferrodoxin (rbo) and a glutamate dehydrogenase with an N-terminal rubredoxin fold (CD630_08280). Rbr1 even represents the second most abundant protein after the S-layer protein SlpA (6). We enquired, why these genes are highly expressed in the absence of any oxidative stress and focused on the repressor protein PerR, which regulates its own transcription and the one of genes involved in oxidative stress and metal homeostasis as described in Bacillus subtilis and in other Gram-positive bacteria (8,9).…”
Section: Resultsmentioning
confidence: 99%